Image Post-Processing in Dental Practice - Gormez, Ozlem; Yilmaz, Hasan Huseyin (European Journal of Dentistry, 2009)
Image post-processing of dental digital radiographs, a function which used commonly in dental practice is presented in this article. Digital radiography has been available in dentistry for more than 25 years and its use by dental practitioners is steadily increasing. Digital acquisition of radiographs enables computer-based image post-processing to enhance image quality and increase the accuracy of interpretation. Image post-processing applications can easily be practiced in dental office by a computer and image processing programs. In this article, image post-processing operations such as image restoration, image enhancement, image analysis, image synthesis, and image compression, and their diagnostic efficacy is described. In addition this article provides general dental practitioners with a broad overview of the benefits of the different image post-processing operations to help them understand the role of that the technology can play in their practices. (Eur J Dent 2009;3:343-347)
Keywords: Dentistry; Digital radiography; Image processing